2015
DOI: 10.1016/j.celrep.2015.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Germline Modifications in Rats Using CRISPR/Cas9 and Spermatogonial Stem Cells

Abstract: SUMMARY Organisms with targeted genomic modifications are efficiently produced by gene editing in embryos using CRISPR/Cas9 RNA-guided DNA endonuclease. Here, to facilitate germline editing in rats, we used CRISPR/Cas9 to catalyze targeted genomic mutations in rat spermatogonial stem cell cultures. CRISPR/Cas9-modified spermatogonia regenerated spermatogenesis and displayed long-term sperm forming potential following transplantation into rat testes. Targeted germline mutations in Epsti1 and Erbb3 were vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 46 publications
2
85
0
Order By: Relevance
“…Several potential solutions to this problem have been published. In rodents, the introduction of programmable nucleases, performed either in vivo or in vitro, into adult spermatogonial or oogonial stem cells has been accomplished (Fanslow et al, 2014;Chapman et al, 2015;Sato et al, 2015;Takahashi et al, 2015;Wu et al, 2015). These mutated germ cell precursors variably contribute to the germline while endogenous unmutated germ cells remain.…”
Section: Discussionmentioning
confidence: 99%
“…Several potential solutions to this problem have been published. In rodents, the introduction of programmable nucleases, performed either in vivo or in vitro, into adult spermatogonial or oogonial stem cells has been accomplished (Fanslow et al, 2014;Chapman et al, 2015;Sato et al, 2015;Takahashi et al, 2015;Wu et al, 2015). These mutated germ cell precursors variably contribute to the germline while endogenous unmutated germ cells remain.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted genomic manipulation in the rat was transformed by the advent of ZFN and TALEN technology, which provided a means to create mutant strains without the need for ESC cultures. And, though ZFNs and TALENs have proven effective, the field has been quick to adapt the newest CRISPR tools [7579] to produce a range of germline mutant strains, as well as knock-in fluorescent reporters and Cre and LoxP conditional mutants that have proven so effective in the mouse [80]. As is already clear in cell culture models, the simplicity of CRISPR will likely see it become the dominant genome-engineering tool in the rat, and this will translate to an expanded array of rat disease models [81].…”
Section: One Tool To Rule Them Allmentioning
confidence: 99%
“…Moreover, germline gene modifications are also attainable via genome editing of spermatogonial stem cells (SSCs), potentially preventing mosaicism in offspring by avoiding the totipotent states that accompany embryogenesis. Successful editing using the SSC approach has been demonstrated in mice [38] and in rats [39]. Of note, Reddy et al demonstrated that mitochondria-targeted TALENs (mito-TALENs) can be used in mouse oocytes fused with cells from a patient to eliminate human mitochondrial DNA (mtDNA) mutations [40].…”
mentioning
confidence: 98%